Consent is not as Simple as Tea: Student Activism against Rape Culture. Issue 1 (1st March 2021) - Adams, Brittany
Abstract: In this article, I report on an action project undertaken by a group of young women (aged 18 to 20) to foster public discussions about the prevalence of rape culture on their university's campus. Students proposed this action project during a book study of a young adult (YA) novel that focused on rape culture and sexual violence. Discussions during the book study resulted in the women creating a video designed for university orientation events that addressed common misconceptions about issues such as consent, relationship violence, sexual coercion, and victimhood. Using case study and narrative methods, I recount my experience of witnessing unexpected activism in my classroom. Framed within critical literacy research, I consider the outcomes of making space for student activism and I discuss implications for practitioners.